Exploring students’ attitudes towards their own English accent: insights from SMA Negeri 1 Stabat - Effendi, Fika Emylia; Rangkuti, Rahmadsyah; Rosa, Rusdi Noor (UNIB Press, 2025)
The norms of linguistic correctness often stigmatize non-standard accents and varieties of English, reinforcing a perception of inadequacy among non-native speakers. This stigmatization is particularly evident among students learning English as a foreign language, many of whom may view native-like accents as the ideal, which can diminish their confidence in their own speech. This study investigates the attitudes of students towards their own English accents, aiming to uncover the underlying reasons for these attitudes and identify their preferred English accents. Utilizing a descriptive research design, a set of questionnaires was administered to 34 students at SMA Negeri 1 Stabat, North Sumatra, Indonesia. The findings reveal that most students have negative attitudes towards their own English accents, largely influenced by affective factors such as self-esteem, anxiety, and fear of judgment. In contrast, behavioral and cognitive factors contribute to more neutral stances. The majority of students express a preference for the American accent, a choice shaped by the global dominance of American media, the Indonesian education system’s focus on American English, and the perceived career benefits tied to American English proficiency. Furthermore, students associate the American accent with prestige, higher social status, and enhanced employment prospects. These findings underscore the need for educational interventions that challenge the bias toward specific accents and promote a more inclusive appreciation of the diversity within the English language. The study’s implications are critical for educators and policymakers in developing curricula that foster positive attitudes toward diverse English accents, ensuring that learners feel confident in their unique linguistic identities.